The relationship between oxidative stress, smoking and the clinical severity of psoriasis. (25th September 2012) - Emre, S.; Metin, A.; Demirseren, D.D.; Kilic, S.; Isikoglu, S.; Erel, O.
Abstract Background Recent studies suggested that increased oxidant products and decreased antioxidant system functions may be involved in the pathogenesis of psoriasis. In this study, we investigated total oxidative status, Paraoxonase (PON)1/arylesterase enzyme activities and severity of the disease in smoker and non‐smoker psoriatic patients. Methods Fifty‐four patients with plaque type psoriasis (28 smokers and 26 non‐smokers) and 62 healthy volunteers (16 smokers and 46 non‐smokers) were enrolled in the study. Serum total oxidant status (TOS), total antioxidant capacity (TAC) and arylesterase levels were measured, and oxidative stress index (OSI) was calculated in all participants. Results Psoriasis Area and Severity Index scores were significantly higher in smoker patients than in non‐smoker patients (P = 0.014). Both smoker and non‐smoker patients had significantly increased TOS levels and OSI values and decreased TAC levels than healthy subjects (all P values = 0.000). The TAC and TOS levels, OSI values and arylesterase activities were similar between smoker and non‐smoker patients. The levels of triglyceride (TG), total cholesterol (TC), low‐density lipoprotein (LDL) and high‐density lipoprotein (HDL) were not significantly different between smoker and non‐smoker psoriasis patients. When compared with non‐smoking controls, only smoking psoriasis patients had significantly higher TG (P = 0.005), lower HDL (P = 0.022) and lower arylesterase levels (P = 0.015). There were no significant correlations with Psoriasis Area and Severity Index (PASI) scores and TAC, TOS, OSI, TG, TC, HDL and LDL levels in all psoriasis patients. Conclusions Oxidative stress is increased in psoriasis patients regardless of their smoking status. The decreased arylesterase activity in smoker psoriasis patients suggested that smoking may be a considerable risk factor that increases the severity of psoriasis by increasing oxidative stress in these patients.